Effect of Consciousness in Sustainable Consumption Habits on Purchase Intention of Green Products : Comparison Study Between India and USA - Fernandes, Semila; Sathish, M.; Shrivastava, Priyanka (Indian Journal of Marketing, 2024)
Purpose : The paper highlighted the importance of understanding consumer orientation for sustainability as a function of their consciousness regarding sustainable consumption (SC) habits and its impact on the purchase intention (PI) of green products. Methodology : The goal of a cross-national comparison study between India and the USA was to determine how consumer awareness of SC practices affected consumers’ intentions to buy green items. Data was collected from MBA students in both countries. A total of 112 samples from India and 145 samples from the USA were considered for the study. Findings : The proposed model was tested using structural equation modeling with respondents from India and the USA. A moderation effect of the degree of SC habits on environmental dimensions was observed. The structural model’s mediation test, which examined the relationship between SC behaviors and the intended results of green product PI (while controlling for other variables) revealed a poorer model fit for both India and the USA. Practical Implications : A correlation between greater environmental consciousness and more SC patterns was discovered, and vice versa. Studies revealed that cultural background, gender, and socioeconomic status — all had a big impact on the buying patterns of consumers. Originality : Triple bottom line (TBL) notions were used in the study to add to the conversation about SC behaviors. Understanding cross-cultural variations in sustainable consumer behavior was improved by the insights it offered into the PIs of green items using a TBL approach across India and the USA.